Gastric Angiolipoma Resected with Endoscopic Submucosal Dissection - Yeo, Sang Myung (Clin Endosc, 2021)
Angiolipoma is a benign fatty neoplasm that has components of proliferating blood vessels. These types of lesions commonly occur in the subcutaneous tissue of the limbs and trunk. Angiolipoma in the gastrointestinal tract is extremely rare, and the final diagnosis generally depends on histological examination of the excised biopsy. In most previously reported cases, the lesions were diagnosed and treated with surgical management. In this study, we report a case of gastric angiolipoma of approximately 4 cm in size that was diagnosed and treated with endoscopic submucosal dissection.